Modulating electronic structure of metal-organic framework derived catalysts for electrochemical water oxidation - Singh B.; Singh A.; Yadav A.; Indra A. (My University, 2025)
Oxygen evolution reaction plays the role of a bottleneck in the electrochemical water splitting. The production of high current density at low overpotential and long-time durability of the catalysts are the main challenges to achieve further progress in this field. In this respect, metal–organic frameworks (MOFs) provide a new route for the designing of the catalysts with excellent electrochemical water oxidation activity. MOF derived materials have been demonstrated with high surface area, porous structure, increased electron transport, accessible active sites, and tailorable properties. Recent studies of MOF derived electrocatalysts mainly focused on the morphological development, crystal structure modulation, facet engineering, and enhancement of the electrochemical surface area. The recent reviews also followed the same trend to explain the improved water oxidation activity of the MOF derived catalysts. As a result, electronic structure, the major descriptor of the water oxidation activity, was never reviewed for the MOF derived electrocatalysts. Hence a systematic discussion for the designing of the MOF-derived electrocatalysts by electronic structure modulation is highly demanded. In this review, we have described the electronic structure engineering of the MOF derived materials to attain efficient water oxidation activity. The controlling factors like eg orbital filling, metal–oxygen covalency, mixed valency of metal ions, octahedral (Oh) vs tetrahedral (Td) occupancy of the metal ions, and vacancy engineering have been discussed. The strategies of tuning the electronic properties by interfacial modulation, surface overlayer, Fermi level manipulation, self-supported strategy, and heterostructure formation have also been addressed to improve the catalytic activity and stability of the MOF derived catalysts. Finally, an attempt has been made to establish a structure–activity-stability relationship in MOF derived materials for the electrochemical water oxidation. © 2021 Elsevier B.V.